PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 001 SIMPANG KANAN KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Widia Astuti; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is motivated by the fact that science student learning outcomes appear to be low and there stiil many student who have not reached the KKM. Of the 26 students only 5 students (20%) which reached the KKM. And 21 student. This research is a clasroom action research conducted in class IV SDN 001 Simpang Kanan. Research instrument consisted of a learning Tool used in this research is guided by the education Unit Level Curruculum (SBC), known as curriculum 2006 learning device cinsist of a syllabus,lesson plans, student worksheets and observation sheet. The first meeting for the first cycle of activity the teacher with an average teacher activity was absorved on the second cycle increased compared with the cycle I. At the first meeting I cycle average teacher aktivity 62,5% in the category enough, at the second meeting of the average activity teachers increased to 66,67% also in the category enough at the first meething of the second cycle the average activity of 83,33% of teacher with good category and the second meeting with an average activity of 95,83% in the category of very good. The first meeting of the first cycle an average of 58,33% of student activity with enough categories,at the second meeting of the average activity increased to 66,67% in enough category. At the first meeting of the second cycle an average of 83,33% of student activity in the good category ant the scond meeting increased compared with the previous meeting by an average of91,67% of student activity with very good category. Student learning outcomes after initial data of student worth over KKM only 5 people after the first cycle an increase of up to 15 people after the second cycle to be increased up to 20 people Similarly, the average value average student classically obtained at baseline and after just 57,88 I cycle to increase by an average of 70,7 and in the second cycle to be increased to 80,19. This means that the classical value obtained student has above KKM has been determined.Keywords: Learning Model of Cooverative Tipe NHT, Learning outcomes IPS